Legionella: A Promising Supplementary Indicator of Microbial Drinking Water Quality in Municipal Engineered Water Systems - Zhang, Chiqian; Lu, Jingrang (Frontiers in Environmental Science, 2021)
Opportunistic pathogens (OPs) are natural inhabitants and the predominant disease causative biotic agents in municipal engineered water systems (EWSs). In EWSs, OPs occur at high frequencies and concentrations, cause drinking-water-related disease outbreaks, and are a major factor threatening public health. Therefore, the prevenance of OPs in EWSs represents microbial drinking water quality. Closely or routinely monitoring the dynamics of OPs in municipal EWSs is thus critical to ensuring drinking water quality and protecting public health. Monitoring the dynamics of conventional (fecal) indicators (i.e., total coliforms, fecal coliforms, and Escherichia coli) is the customary or even exclusive means of assessing microbial drinking water quality. However, those indicators infer only fecal contamination due to treatment (e.g., disinfection within water utilities) failure and EWS infrastructure issues (e.g., water main breaks and infiltration), whereas OPs are not contaminants in drinking water. In addition, those indicators appear in EWSs at low concentrations (often absent in well-maintained EWSs) and are uncorrelated with OPs. For instance, conventional indicators decay while OPs regrow with increasing hydraulic residence time. As a result, conventional indicators are poor indicators of OPs (the major aspect of microbial drinking water quality) in EWSs. An additional or supplementary indicator that can well infer the prevalence of OPs in EWSs is highly needed. This systematic review argues that Legionella as a dominant OP-containing genus and natural inhabitant in EWSs is a promising candidate for such a supplementary indicator. Through comprehensively comparing the behavior (i.e., occurrence, growth and regrowth, spatiotemporal variations in concentrations, resistance to disinfectant residuals, and responses to physicochemical water quality parameters) of major OPs (e.g., Legionella or L. pneumophila, Mycobacterium, and Pseudomonas or P. aeruginosa), this review proves that Legionella is a promising supplementary indicator for the prevalence of OPs in EWSs while other OPs lack this indication feature. Legionella as a dominant natural inhabitant in EWSs occurs frequently, has a high concentration, and correlates with more microbial and physicochemical water quality parameters than other common OPs. Legionella and OPs in EWSs share multiple key features such as high disinfectant resistance, biofilm formation, proliferation in amoebae, and significant spatiotemporal variations in concentrations.